2019
DOI: 10.1007/s10096-019-03525-y
|View full text |Cite
|
Sign up to set email alerts
|

Extended-pulsed fidaxomicin versus vancomycin for Clostridium difficile infection: EXTEND study subgroup analyses

Abstract: Poor outcomes following Clostridium difficile infection (CDI) have been associated with advanced age, presence of cancer and C . difficile PCR-ribotype 027. The impact of baseline risk factors on clinical outcomes was evaluated using data from the EXTEND study, in which rate of sustained clinical cure (SCC) in the overall population was significantly higher with an extended-pulsed fidaxomicin (EPFX) regimen than with vancomycin. Patients aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The study showed that vancomycin and fidaxomicin are similar in terms of initial treatment response, but follow up at 90 days showed a significantly lower rate of recurrence in those who received fidaxomicin compared with vancomycin (6.2% versus 19.0%, p < 0.001). 31 This study shows that, with an alternative usage of fidaxomicin, very low rates of recurrence can be achieved. The other study used to support fidaxomicin being used preferentially ahead of vancomycin was a meta-analysis by Okumura et al including seven publications.…”
Section: The Modern Era 2014–presentmentioning
confidence: 68%
“…The study showed that vancomycin and fidaxomicin are similar in terms of initial treatment response, but follow up at 90 days showed a significantly lower rate of recurrence in those who received fidaxomicin compared with vancomycin (6.2% versus 19.0%, p < 0.001). 31 This study shows that, with an alternative usage of fidaxomicin, very low rates of recurrence can be achieved. The other study used to support fidaxomicin being used preferentially ahead of vancomycin was a meta-analysis by Okumura et al including seven publications.…”
Section: The Modern Era 2014–presentmentioning
confidence: 68%
“…Of note, pharmacokinetic/pharmacodynamic data from patients enrolled in EXTEND revealed that fidaxomicin concentrations in stools were above the MIC 90 of C. difficile isolates (inferred from in vitro studies) until day 26 ± 1 [ 90 ]. The subgroup analyses of the EXTEND study showed higher clinical cure rates in the extended-pulsed fidaxomicin arm independent of age, prior CDI, infection with PCR-ribotype 027, CDI severity, or presence of cancer [ 91 ]. A post hoc analysis of the EXTEND study conducted after testing stools of enrolled patients at screening, also with the BioFire FilmArray Gastrointestinal Panel (BioMérieux, Basingstoke, UK), suggested that co-infection with other pathogens could possibly explain clinical failures [ 92 ].…”
Section: Results Of Phase-3/4 Randomized Controlled Trialsmentioning
confidence: 99%
“…Of the remaining 22 full-text articles reviewed, 14 studies (six RCTs and eight observational trials) met eligibility criteria for the final meta-analysis (Figure 1). [9][10][11][12][20][21][22][23][24][25][26][27][28][29][30] Reasons for excluding full-text articles included an unspecified follow-up period for recurrence, missing data, population overlap, and concomitant use of fecal microbiota transplantation. [31][32][33][34][35][36][37] For included RCTs, three studies were assessed to have a low risk of bias and three with some concerns, primarily due to problems related to the unblinding of standard-of-care treatments (Figure 2A).…”
Section: Re Sultsmentioning
confidence: 99%